Penerapan Blockchain dengan Integrasi Smart Contract pada Sistem Crowdfunding - Fiqar Aprialim; Adnan; Ady Wahyudi Paundu (Ikatan Ahli Informatika Indonesia (IAII), 2021)
The existing crowdfunding platforms still operate using centralized system. While centralized system can operate well, it requires a third party intermediary in order to operate and thus does not completely provide data security and transparency of crowdfunding activities. In addition, the existence of a third party intermediary in a crowdfunding activity also causes the existing processing costs to be expensive. Therefore, the crowdfunding system needs to be built in a decentralized manner so that it eliminates the need for third parties as intermediaries in the crowdfunding process. This study proposes a prototype of decentralized crowdfunding system using Ethereum blockchain and smart contract technology. The result of system functionality test using black box testing method shows that all functionality of the crowdfunding system can run properly while operate in decentralized architecture.